2013
DOI: 10.1002/joc.3656
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the surface energy balance over two contrasting urban environments using the Community Land Model Urban

Abstract: A single-layer urban canopy model Community Land Model Urban (CLMU) is evaluated over two contrasting urban environments of Toulouse (France) and Melbourne (Australia). For the latter, three measurement sites are available characterized by a varying amount of vegetation, which supports a detailed assessment of the representation of urban vegetation in CLMU. For Toulouse, observed roof, wall and road surface temperatures allow for a detailed evaluation of the anthropogenic heat parameterization. Overall, CLMU p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 56 publications
(170 reference statements)
0
43
0
Order By: Relevance
“…3 and 4). This agrees with the observations for which only small evaporation rates (ie., lower than 25 Wm À2 ) are found most of the nighttime in Toulouse centre Demuzere et al, 2013, see their Figure 4). In contrast, the evaporation is much larger at daytime in both model results and observations.…”
Section: Determination Of the Water-storage Parameters W M And D Mmentioning
confidence: 91%
See 3 more Smart Citations
“…3 and 4). This agrees with the observations for which only small evaporation rates (ie., lower than 25 Wm À2 ) are found most of the nighttime in Toulouse centre Demuzere et al, 2013, see their Figure 4). In contrast, the evaporation is much larger at daytime in both model results and observations.…”
Section: Determination Of the Water-storage Parameters W M And D Mmentioning
confidence: 91%
“…As a result, the representation of the urban water balance in existing urban land-surface parametrizations is very rudimentary: For instance, various urban models do not consider evaporation from the impervious surfaces as a first approximation to the reduction of ET in cities (Hénon et al, 2012;Martilli et al, 2002;Schubert et al, 2012). Up to now, the accuracy, validity and applicability of water-storage parametrizations employed in existing land-surface models (Masson, 2000;Kanda et al, 2005;Oleson et al, 2008;Demuzere et al, 2013Demuzere et al, , 2014a have not been investigated in detail. The consequential deficiencies in urban water-storage parametrizations lead to very poor model performances in terms of ET: Grimmond et al (2011) showed that the evapotranspiration is the least well-modelled flux of the SEB.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a study by Demuzere, Oleson, Coutts, Pigeon, and van Lipzig (2013) which simulated the impact of different urban environments on the surface energy balance, a similar energetic-hierarchy was found between compact and openset residential thermal climate zones, which are an earlier iteration of the LCZ 2 and LCZ 6 classes respectively. The reduction in vegetation fraction leads to a minor decrease in evapotranspiration though the larger impact is found in terms of heat storage as the heat capacity of these areas significantly increases due to the additional buildings and pavements.…”
Section: Development Pathwaymentioning
confidence: 93%